IMPLEMENTATION AND ANALYSIS OF FIR FILTER USING TMS 320C6713 DSK (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In most of the applications, analog signals are produced in response to some physical phenomenon or activity. But it is quite difficult to process that analog signal; here comes the need to convert an analog signal to a digital signal. For this purpose specific digital signal processors (DSP’s) are developed. TMS 320C6713 is one of such type of processors that can be used to process or handle the signals in a variety of ways. In the current report, basically the architecture of this processor is studied. Along with the processor architecture, the hardware portion DSK (Digital Starter Kit) and the software portion CCS (Code Composer Studio) is also studied. Digital filters are very commonly found in everyday life and include a variety of applications. Mainly they are used for two major purposes: signal separation and signal restoration. Signal separation is needed when a signal has been contaminated with interference, noise, or other signals. Signal restoration is used when a signal has been distorted in some way. So, various programs have been analyzed in this work to implement efficiently those FIR filter structures on TMS 320C6713 DSK. Characteristics of FIR filters are studied in frequency domain.